Analysis of virulence genes, drug resistance detection, and pathogenicity in Enterococcus from farm animals. (October 2022) - Kang, Xinyun; Wei, Yanqin; Fan, Xiaofei; Luo, Shuangyan; Luo, Xiaofeng; Zhao, Sijun; Wang, Guiqin
Abstract: This study aimed to investigate the presence of eight virulence genes ( ace, asa1, esp, efaA, gelE, cylA, agg, fsr ) in Enterococcus from a variety of animals and to explore the drug resistance and pathogenicity . This could provide a theoretical basis for clinical treatment of Enterococcus infections. Anal swabs from pigs, chickens, cattle, and dogs in farms and pet hospitals were collected for Enterococcus isolation and identification. Eight virulence genes were detected (PCR method), and drug resistance was assessed (drug-sensitive paper method). The strains containing different virulence genes were then divided into EV1, EV2, and EV3 groups. The L D 50 and pathogenicity was examined by intra-peritoneal injection to infect mice. Differences were found in the detection rates of virulence genes in Enterococcus from the different animals. The highest overall detection rate was for the esp gene (78.0%), and the lowest for the cylA gene (15.5%). Eight genes were detected most frequently in Enterococcus from dogs and least frequently from cattle. Among the Enterococcus strains from four variety of animals, drug resistance was highest against sulfamethoxazole (100%), cefotaxime (>97%), and cefotaxitin (>93%). Drug resistance was lowest against vancomycin (0%), levofloxacin (<12%) and ciprofloxacin (<13%). The L D 50 for each of the three groups was E V 1 L D 50 = 8.71 × 10 9 C F U ， E V 2 L D 50 = 2.34 × 10 10 C F U ，and E V 3 L D 50 = 9.33 × 10 10 C F U . The Enterococcus 1 2 L D 50 dose group caused significant clinical symptoms in mice, with pathological effects on the heart, liver, lungs, and kidneys, and particularly on the urinary system. The abundance of Enterococcus virulence genes, drug resistance, and pathogenicity vary among different animal origins, and the pathology caused by Enterococcus requires effective treatment protocols based on species and regional characteristics. Highlights: There are differences in the detection rate of virulence genes and drug resistance in Enterococcus isolated from different animal sources. Geographical isolation may be the cause of different virulence gene detection rates, drug resistance and pathogenicity of Enterococcus in the same species.